Aboriginal Kinship Carers and Children with Fetal Alcohol Spectrum Disorder in Western Australia: Advancing Knowledge from an Indigenous and Disability Lens - Williams, Robyn; Badry, Dorothy (First Peoples Child & Family Review, 2023)
Children and youth with fetal alcohol spectrum disorder (FASD) have limited access to assessment, diagnostic, and treatment resources – a distinct disadvantage in meeting their care needs in Australia. Limited knowledge exists on the intersection of FASD, Indigeneity, racism, trauma, and child welfare involvement. Notably, the lack of support for children with FASD increases the risk of adverse outcomes, including incarceration, homelessness, mental health problems, and early mortality. Children with FASD are often cared for in the child protection system by kinship carers, many without a diagnosis or the benefits of FASD informed care. Rarely considered is the Australian response to FASD or the Aboriginal worldview on disability. Qualitative research was utilized to conduct semi-structured interviews with six carers of Indigenous children with FASD–three foster carers and three relative or kinship carers. Seven core themes identified by carers included: FASD awareness, caregiver health, advocacy for the child, mothers of the children with FASD, loss and grief experienced by the carer, social costs, and children in child protection care. Carers identified that limited resources existed to address the disabilities and care needs of children, including training and respite. Financial disparity exists with relative carers receiving less income than foster carers. Carers demonstrated advocacy, resiliency, and resourcefulness in providing care. A lack of knowledge of FASD and core resources in child welfare services were identified as major challenges in providing care. This research examined the caregiving experiences of foster and Aboriginal kinship carers, caring for children with FASD in child protection.